Human Resource Development for Industrialization and Modernization in Vietnam: The Case of Bac Ninh Province - Ha, Nguyen Viet (Darul Yasin Al Sys, 2025)
This study examines human resource (HR) development policies in Bac Ninh province, Vietnam, within the broader context of the country's industrialization and modernization efforts. Employing a mixed-methods approach that integrates policy content analysis with empirical data collected between 2008 and 2023, the research identifies critical institutional, structural, and operational challenges impeding effective HR development. Key findings reveal a persistent mismatch between workforce qualifications and industrial sector demands, limited coordination across policy frameworks, and inadequate engagement from the private sector. These issues hinder the province’s ability to meet the evolving labor market requirements of a rapidly transforming economy. In response, the study proposes targeted policy recommendations, including enhancing decentralization mechanisms, reforming vocational training systems to align with industry needs, and fostering stronger public-private partnerships. By focusing on a localized case within an emerging economy, the study contributes to the broader discourse on adaptive HR policy design and implementation in the context of industrial transformation.